Penerapan Literasi Media Di Era Digital Pada Generasi Zaman Now - Muhammad Askolani; Ipad Padlan Al’Munawar (Communicative : Jurnal Dakwah dan Komunikasi, 2020)
This study aims to determine the application of media literacy in the digital age at the time ofgeneration. now the current This study uses qualitative methods by using library research methods. Data analysis is carried out by finding, collecting, and comparing qualitatively with various findings obtained and linking them with various concepts and studies of related literature or literature. The results of this study indicate that 1) The interaction of today's generation with social media in the digital era is very intense. 2) media literacy in the digital age at the time of the generation now has not been implemented properly in the community even though they are already adept at using digital devices. 3) The development of media literacy at age generation now isin the digital age are still not as expected